BIOGRAFI BUDAYA BENDAWI: DIASPORA NEKARA PERUNGGU DI KEPULAUAN MALUKU - Ririmasse, Marlon (Berkala Arkeologi, 2015)
This article discusses the diaspora and biography of the Dong Son Kettledrums in the Moluccas Archipelago. This research found that the cultural historical setting behind the existence of these objects is related to the diaspora that corresponds with the trade dynamics in the Moluccas archipelago as a source region for the exotic commodities. Shifted from the original context of the production center origin culture di the Mainland Asia to the Insular Southeast Asia, new values had been attached to these bronze kettledrums that related with the local cultural identity aspect.